Activity and biochemical characteristics of plant extract cuminic acid against Sclerotinia sclerotiorum. (November 2017) - Sun, Yang; Wang, Yong; Xie, Ziyu; Guo, Enhui; Han, Lirong; Zhang, Xing; Feng, Juntao
Abstract: Sclerotinia stem rot caused by Sclerotinia sclerotiorum (Lib.) de Bary is present worldwide and causes large economic losses. As more and more serious resistance of S. sclerotiorum against commonly used fungicides, development of novel biorational fungicides to control this fungal has become more and more urgent. In this study, the activity of cuminic acid isolated from the seed of Cuminum cyminum L, was assessed. The median effective concentration (EC50 ) values for inhibition of mycelial growth of 78 S. sclerotiorum strains ranged from 5.46 to 29.34 μg/ml, with an average EC50 value of 17.36 ± 2.28 μg/ml. Meanwhile, both in pot experiments and on detached leaves, cuminic acid exhibited significant control effects against S. sclerotiorum. After treated with cuminic acid, mycelia were clustered seriously and the surface were collapsed and shriveled. In S. sclerotiorum, cell membrane permeability would be increased while oxalic acid content would be decreased and glycerol content would be increased significantly treated with cuminic acid. Above all, cuminic acid showed the potential as a natural alternative to commercial fungicides or a lead compound to develop new fungicides for the control of Sclerotinia stem rot. Highlights: We established the baseline sensitivity of Sclerotinia sclerotiorum to cuminic acid. Evaluated the potential value of cuminic acid against S. sclerotiorum in pot experiments and on detached leaves. Explored the effect of cuminic acid on the biochemical characteristics of S. Sclerotiorum.